6th Malaysia Indonesia Brunei Medical Science Conference Universiti Brunei Darussalam, Brunei 21-23 Julai 2010 - Meera Mohaideen, Abdul Kareem (Pusat Pengajian Sains Perubatan, 2010)
Malaysia Indonesia Brunei Medical Sciences Conference is an annual collaboration between Institute of Medicine, Universiti Brunei Darussalam, Faculty of Medicine, Universiti Kebangsaan Malaysia and Faculty of Medicine, Universitas Indonesia. The Conference has been conducted annually since 2005. This year, the 6th Conference with the theme "Research For Better Health" will again be hosted by Institute of Medicine, Universiti Brunei Darussalam and will be held on 21•t-23rd July 2010 at Chancellor Hall, Universiti Brunei Darussalam. The event serves as an important avenue for exchanging ideas, evidences, and information to initiate research collaborations as well as research publications in the context of South-East Asia (SEA) aspects. Presently it has brought together health professionals and researchers from the three countries in several projects that address health issues in the South-east Asian regions that include problems with avian flu, stressrelated matters amongst health care professionals and cardiovascular disease. The 6th event will see progress reports of these currently"~running projects and will hope to forge more collaborations in other health-related matters that are common for the three countries. It is of great pleasure to invite you to this conference to explore, share and discuss your experiences and views.